RF Energy Harvesting with Multiple Sources and Co-Channel Interference Assisted - Puniran, Khairul Nizam; Ahmad, Robiah; Dziyauddin, Rudzidatul Akmam (Journal of Advanced Research in Business and Management Studies, 2020)
Wireless Energy Harvesting (EH) from the ambient Radio Frequency (RF) has emerged a solution in recent technology which can prolong the consumption of conventional battery in any constraint nodes. In this paper, a 3-node decode-and-forward (DF) model is proposed where the relay node is subject to an energy constraint. Multiple sources and co-channel interference (CCI) are added in the system model known as Multiple-Source and Single-Relay (MSSR). A mathematical model is derived in Time Switching Relaying (TSR) scheme to obtain an average system throughput at a destination. Several numerical simulations with respect to the average throughput and system parameters were performed and compared with both ideal receiver and SingleSource and Single-Relay (SSSR) schemes. By applying multiple sources and CCI as an energy enhancement at the constraint node, the optimal value of EH ratio for TSR can be reduced significantly by 10% as compared to the ideal receiver and SSSR.